2013
DOI: 10.1038/modpathol.2012.143
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in signaling pathways of gastroenteropancreatic neuroendocrine tumors: a critical look at notch signaling pathway

Abstract: The molecular pathogenesis of gastroenteropancreatic neuroendocrine tumors is largely unknown. We hypothesize that gastroenteropancreatic neuroendocrine tumors are heterogeneous with regard to these signaling pathways and these differences could have a significant impact on the outcome of clinical trials. We selected 120 well-differentiated neuroendocrine tumors including tumors originating in pancreas (n ¼ 74), ileum (n ¼ 31), and rectum (n ¼ 15). Immunohistochemistry was performed on tissue microarrays using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 23 publications
1
40
1
Order By: Relevance
“…These data further support the concept that Notch1 activation up-regulates PDX-1 expression and that Notch1 activation may contribute to the overexpression of PDX-1 in PNETs. Notch1 has been reported to be expressed in PNET with accompanied expression of HES1, a downstream target of Notch1 [57]. Our studies showed that the majority of human PNET specimens expressed NICD in correlation with PDX-1 overexpression.…”
Section: Resultssupporting
confidence: 57%
“…These data further support the concept that Notch1 activation up-regulates PDX-1 expression and that Notch1 activation may contribute to the overexpression of PDX-1 in PNETs. Notch1 has been reported to be expressed in PNET with accompanied expression of HES1, a downstream target of Notch1 [57]. Our studies showed that the majority of human PNET specimens expressed NICD in correlation with PDX-1 overexpression.…”
Section: Resultssupporting
confidence: 57%
“…However Notch signaling also appears to have a tumor suppressor role in gastrointestinal, thyroid and pulmonary neuroendocrine tumors[42,48,49]. In another recent study of 31 ileal carcinoids, Notch signaling was uniformly absent in ileal neuroendocrine tumors suggestive of loss of tumor suppressive role[50]. Is the loss of Notch signaling, the driving mutation and occurs after the first stem cell division at the level of transit amplifying cells with subsequent progeny showing dysfunction?…”
Section: Pathogenesismentioning
confidence: 99%
“…However, this histogenesis of NET is not common in any NETs. Wang et al 20 reported that gastroenteropancreatic NETs were heterogeneous with regard to the Notch1-HES1 signalling pathway; Notch1 and Hes1 were preferentially expressed in rectal NETs and a subset of pancreatic NETs, but uniformly negative in ileal NETs, indicating the heterogeneity in signalling pathways of gastroenteropancreatic NETs. Moreover, in the developing endoderm, disruption of Notch-Hes1 signalling results in precocious endocrine differentiation in the pancreas.…”
Section: Discussionmentioning
confidence: 99%